AN OVERVIEW OF PRESBYPHAGIA - Soewito, Ferius; Adhitya (Majalah Kedokteran Indonesia, 2018)
Dysphagia is a frequent problem in elderly population since it can cause aspiration that leads to more complications. It appears as one of major potential problemswhich cause disability in elderly. Degenerative process which causes changes in swallowing structures and physiology in healthy aging (presbyphagia)can affect the swallowing process and leads to dysphagia. Consequences of dysphagia vary from social isolation to life threatening conditionssuch as aspiration. Detecting presbyphagia is essential to prevent aspiration.